2010
DOI: 10.1208/s12249-010-9432-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Silymarin Self-Microemulsifying Drug Delivery System with Enhanced Oral Bioavailability

Abstract: Abstract. The objective of this work was to develop a self-microemulsifying drug delivery system (SMEDDS) for improving oral absorption of poorly water-soluble drug, silymarin. The pseudo-ternary phase diagrams were constructed using ethyl linoleate, Cremophor EL, ethyl alcohol, and normal saline to identify the efficient self-microemulsification region. The particle size and its distribution of the resultant microemulsions were determined using dynamic light scattering. The optimal formulation with the best s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…We previously demonstrated that silymarin flavonolignans do not reach peak plasma concentrations above 0.2 mM with use of this dose regimen (Hawke et al, 2010); these concentrations are significantly lower than those associated with drug interaction risk identified in the present study. However, higher oral doses and improved formulations of silymarin (e.g., nanoemulsions) are being evaluated to increase systemic/tissue concentrations to achieve desired clinical outcomes (Flaig et al, 2010;Li et al, 2010;Wang et al, 2012). On the basis of the present study, these higher doses and/or improved formulations may increase the risk of OATP-mediated interactions.…”
Section: Discussionmentioning
confidence: 97%
“…We previously demonstrated that silymarin flavonolignans do not reach peak plasma concentrations above 0.2 mM with use of this dose regimen (Hawke et al, 2010); these concentrations are significantly lower than those associated with drug interaction risk identified in the present study. However, higher oral doses and improved formulations of silymarin (e.g., nanoemulsions) are being evaluated to increase systemic/tissue concentrations to achieve desired clinical outcomes (Flaig et al, 2010;Li et al, 2010;Wang et al, 2012). On the basis of the present study, these higher doses and/or improved formulations may increase the risk of OATP-mediated interactions.…”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5][6] However, its clinical efficacy is compromised by its poor oral bioavailability due to poor water solubility and low permeability. 7,8 In order to improve the oral bioavailability of SM, several delivery systems have been explored such as self-microemulsifying drug delivery systems, [9][10][11] porous silica nanoparticles, 12 solid dispersions, 13 glyceryl monooleate/poloxamer 407 liquid crystalline matrices, 14 proliposomes, 15 silybinphospholipid complexes, 16 and solid lipid nanoparticles. 17 It seems that lipid-based drug delivery systems are more promising in improving the oral absorption of SM owing to their specific absorption-enhancing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…34) UV absorption spectra of ATR and EZT in each excipient and blank SMEDDS were also measured to find the molecular location of solubilized drugs in a micellar environment. 35,36) The molecular locations of solutes (drugs) in the specific micelle structure can be regarded the same as another micelle structure if the wavelength of maximum absorbance (λ max ) of the two spectra are similar because the location of λ max reflects solvent polarity surrounding solutes in micelles. If the drug is solubilized in a specific excipient, its λ max will be similar to the λ max of the drug in the microemulsion.…”
Section: )mentioning
confidence: 99%